PREDIKSI KECEPATAN SEDIMENTASI WADUK SERMO BERDASARKAN DATA PENGUKURAN BATIMETRI MULTI TEMPORAL - , INDRO WICAKSONO ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The volume of water that able to accommodated by the dam are influenced by several factors, one of them is sedimentation. Sedimentation occurs due to erosion which resulted in sediment transport from upstream area to downstream area. A great sedimentation will lead to superficiality on the dam so that the volume capacity of the dam is declining. Sedimentation also affects on the operational pattern of the dam, the more bigger and faster the rate of sedimentation the less volume of water that can be distributed and there will be declining the function of the dam. The discovery of sedimentation velocity on Sermoâs dam can be used to predict the rate of sedimentation in the future and used as the basis to planning the dam maintenance. This research begins by gathered five data of bathymetry measurement on sermoâs dam. This fifth data of measurement are then made a boundary to do cropping process in the research area. The MTD from cropping results is then done by calculated the dam water catchment volume and the average speed of yearly sedimentation. Each of epoch then processed by carried out the analysis of MTD piksel, so the change of piksel value on any epoch can be known. Sedimentation models per year retrieved from the average results of eight epoch sedimentation. The MTD prediction of 2014 were built by MTD of 2013 and MTD models of sedimentation per year. The results of this research show that the changes of Sermoâs dam sedimentation vary greatly in each year. From 2005 to 2006 the volume of sediment which enters the dam totalling by 229.045 . In 2006 till 2011 the sediment increased to 492.595 . From 2011 to 2012 occurs sedimentation amounted to 358.763 . In 2012 to 2013 occurs the addition of sedimentation to the size of 124.290 . From the results, it can be noted that in the pass eight years the sedimentation was occurred in Sermoâs dam with the sedimentation velocity of 150.586,62 per year. The MTD prediction and water catchment of Sermoâs dam have error of maximal water capacity volume, ranges from 0,03% to 1,42% . The sedimentation calculation error could be caused by the presence of measurement data that is not entered IHO and SNI specifications. as well as some not good data quality is caused by density measurements less lane or under the IHO and SNI specifications